Electromagnetic and Electrical Geophysical Investigation of Groundwater Potential at Dangote Cement Depot, Ilokun, Ado-Ekiti, Southwestern Nigeria - Adeoye, Aderemi Sunday; Ajayi, Christopher Ayodele; Ikubuwaje, Chrisopher Olatunde (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2024)
Geoelectric investigation of groundwater occurrence around Dangote Cement Depot, Ilokun, Ado-Ekiti, South-western Nigeria was carried out. Vertical Electrical Sounding Array was chosen for the work. Four traverses with a total length of 105 m were established around the building to locate best position for groundwater development. The results were presented as field curves and geoelectric section. A total spread of 200 to 300 m was employed. Seven VES was carried out to produce four geoelectric sections around the study area. This was used to delineate six geoelectric layers which are; topsoil, weathered layer, fractured basement, partly fractured basement and fresh basement with resistivities: 223 to 2095, 29.7 to 254, 299 to 1141, 134 to 1206, 496 to 2400 and 504 to 34016 ohm-m respectively. Clay formations were delineated very near the surface down to a depth of over 35 m. The clay constitutes major path along the traverse lines as weathered zones. Some parts of the building show fractured zones that can accommodate the formation of groundwater. VES 1, VES 4 and VES 5were promising locations for the drilling of boreholes judging from the thickness of their weathered and fractured zones. VES 5 is the most appropriate for groundwater development.